Quality of life in obsessive-compulsive disorder: a review (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Obsessive-compulsive disorder (OCD) has been considered by the World Health Organization as the 10th leading cause of years lived with disability, but studies on quality of life (QOL) in OCD are still scant. OBJECTIVES: A literature review of studies on quality of life in OCD. METHOD: A MEDLINE, Psychoinfo and LILACS literature review from 1980 to 2007 was conducted, using the following key-words: obsessive-compulsive disorder, quality of life, functional impairment and disability. RESULTS: Population-based studies have shown indirect indicators of QOL impairment in OCD sufferers, such as more unemployment, lower income, lower number of marriages, besides considerably high rates of suicidal thoughts and attempts. Clinical studies found more QOL impairment in OCD patients compared to individuals with some chronic physical conditions, other anxiety disorders, depressive disorders and even schizophrenia, in some aspects. CONCLUSION: The negative impact of OCD on QOL can be severe, affecting several life domains and affecting family members as well. Psychosocial rehabilitation should be an essential part of OCD treatment and it is necessary to increase both public awareness of this disorder and the availability of appropriate treatments to minimize such impact, which can be devastating.